Game Edukasi Kepahlawanan Aman Dimot Berbasis Android - Novita Indriani (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
The rapid development of digital technology has influenced the learning patterns of the younger generation, one of which is the declining interest in local history and heroic values. The lack of interactive history learning media is one of the factors contributing to students' limited understanding of local historical figures, including Aman Dimot as one of the Gayo heroes who fought to defend Indonesian independence in the Takengon region. Therefore, innovation in technology-based learning media is needed to integrate educational and entertainment elements to improve local historical literacy. This study aims to develop an Android-based Aman Dimot Heroic Educational Game as an alternative learning medium to introduce the history of struggles and heroic values to the younger generation. The development method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Application testing was conducted using the black-box testing method to evaluate system functionality and questionnaires involving 20 respondents based on the aspects of functionality, reliability, compatibility, and playability. The testing results showed that all main application functions operated properly based on black-box testing. Furthermore, the software quality evaluation obtained an overall feasibility score of 98.75%, categorized as highly feasible, consisting of functionality at 100%, reliability at 100%, compatibility at 98%, and playability at 97%. In addition, 95% of respondents expressed interest in using the Aman Dimot educational game as a history learning medium. The results indicate that the developed educational game can serve as an effective interactive learning medium to enhance learning interest and introduce local history and Indonesian heroic values to the younger generation.